2022
DOI: 10.1097/qad.0000000000003420
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of mental health disorders in people with HIV and the effects on the HIV care continuum

Abstract: Objective:To describe the prevalence of diagnosed depression, anxiety, bipolar disorder, and schizophrenia in people with HIV (PWH) and the differences in HIV care continuum outcomes in those with and without mental health disorders (MHDs).Design:Observational study of participants in the North American AIDS Cohort Collaboration on Research and Design.Methods:PWH (≥18 years) contributed data on prevalent schizophrenia, anxiety, depressive, and bipolar disorders from 2008 to 2018 based on International Classifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…This can introduce stochasticity that leads to the wide range of outcomes reported in Table 2. Recent cohort data suggest that prevalence of depression among persons with HIV increases with time since initiation of ART [4,72]. However, other evidence suggests that depression onset may be less common among older persons and more common in the years immediately following diagnosis [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…This can introduce stochasticity that leads to the wide range of outcomes reported in Table 2. Recent cohort data suggest that prevalence of depression among persons with HIV increases with time since initiation of ART [4,72]. However, other evidence suggests that depression onset may be less common among older persons and more common in the years immediately following diagnosis [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we have also found more than twice the risk of death in index participants with moderate or severe depression. The causal pathway of this association is described by multiple studies showing the negative impact of depression at each stage of HIV treatment continuum: care engagement [ 28 ], ART initiation and adherence [ 29 31 ], and viral suppression [ 32 , 33 ], resulting in higher mortality [ 34 36 ]. However, some studies reported an independent effect of depression on mortality, controlling for the effects of adherence [ 37 , 38 ] and clinical variables [ 35 , 39 ], potentially suggesting other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Over the same time period, the overall attendance rate of scheduled HIV primary care visits at the Owen Clinic was 88%, whereas our 12‐month rate of retention in care was 77.3%. Nearly 80% of patients in our survey had either SUD, unstable housing, or a MHD, all of which are known barriers to both engagement and retention in care [16, 17, 21]. SUD itself was highly correlated with the presence of an MHD, unstable housing, lack of HIV virological suppression, and missed discharge clinic appointments and 30‐day clinic follow‐up.…”
Section: Discussionmentioning
confidence: 99%